Force–Spectrum Relations for Molecular Optical Force Probes1. Issue 10 (31st January 2014) - Stauch, Tim; Dreuw, Andreas
Abstract Force probes allow real‐time monitoring of forces acting in different regions of large molecules and are potentially suited for the investigation of structural changes occurring in macromolecules during, e. g., folding processes.1–10 Such information is crucial for the understanding of mechanochemical reactivity.2, 3, 6, 7 To this end, small molecular force probes can be incorporated into large molecules.2, 3, 11–13 Some of the available systems are based on mechanochromism, the change of the UV/Vis absorption spectrum of a molecule under mechanical stress.1, 14 Herein we propose the idea of using molecular force probes in which the point‐group symmetry is reduced as a result of mechanical deformation. This effect leads to significant and characteristic changes in the UV/Vis, IR, and Raman spectra of the deformed molecules, which were determined using computational methods. Beneficially, these changes are reversible and occur even if the applied forces are small.